Pedagogy as a Poetic Gesture of Language - Sandra Regina Simonis Richter; Simone Berle (Universidade Federal do Rio Grande do Sul, 2015)
The essay addresses the relationship between the experience of language and poetic imagination based on the reflections by Agamben, Merleau-Ponty and Bachelard as a strategy to expose the tensions within the problem of temporal discontinuity that weaves the fabric of 'languagely' alterity in the meetings between small children and adults. It claims the pedagogic understanding that it is only by interacting poetically with the world, by triggering times of presence, and by assuming our attempts to project singular meanings onto the collective, and not by keeping an analytical distance from it, that we can pursue language as a gesture unfettered by any kind of instrumentality. The pedagogical question that emerges is not about the freedom rooted in the individual, but about living together.